2002
DOI: 10.1021/la011280e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Charge Density and Distribution on the Internal Structure of Electrostatically Self-assembled Polyelectrolyte Films

Abstract: Electrostatically self-assembled (ESA) polyelectrolyte films show in general no internal structure. The use of special polycations, however, namely of lyotropic ionenes, may give rise to highly ordered coatings. In this article, the influence of the charge density of the polyanion, as well as the distribution of the charged groups within this polymer, is examined, using a series of anionic cellulose derivatives. Various techniques were used to study the films' growth and internal structure. Both showed to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…CHI‐CS2.6 multilayers had the lowest mass adsorption possibly due to the very high charge density of CS2.6, which requires less CS to compensate the charges of CHI. Koetse et al have also shown that the CS with higher charge density produce thinner layers during multilayer assembly . The multilayer growth of blend systems as studied by QCM‐D had also shown exponential growth like CHI‐HEP system (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…CHI‐CS2.6 multilayers had the lowest mass adsorption possibly due to the very high charge density of CS2.6, which requires less CS to compensate the charges of CHI. Koetse et al have also shown that the CS with higher charge density produce thinner layers during multilayer assembly . The multilayer growth of blend systems as studied by QCM‐D had also shown exponential growth like CHI‐HEP system (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The cationic polyamino acids (PLO, PLA) possess higher charge densities in comparison to the polysaccharide, DEAD-D [48]. This higher charge density drives a stronger electrostatic interaction with heparin and would more effectively neutralize the surface anionic charges of heparin [49][50][51][52]. Therefore, heparin condensation is expected to be more efficient with the cationic polyamino acids compared to the polysaccharide (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the nature of polyelectrolyte pair used, charge density, rinsing medium, preparation method (dipping, spin-coating, spraying), temperature, pH and ionic strength strongly affect the final system properties. [10][11][12][13][14][15][16][17] The investigation of such effects relies on the use of very sensitive techniques, being able to detect in situ changes of the order of nanometers or nanograms. For this purpose, in the last decade the use of quartz crystal microbalance with dissipation (QCM-D) has been established for the study of multilayer assembly, structure and responsive properties.…”
Section: Introductionmentioning
confidence: 99%